Association of ABO mismatch with the outcomes of allogeneic hematopoietic cell transplantation for acute leukemia. Issue 4 (16th January 2023) - Guru Murthy, Guru Subramanian; Logan, Brent R.; Bo‐Subait, Stephanie; Beitinjaneh, Amer; Devine, Steven; Farhadfar, Nosha; Gowda, Lohith; Hashmi, Shahrukh; Lazarus, Hillard; Nathan, Sunita; Sharma, Akshay; Yared, Jean A.; et al.
Abstract: Allogeneic hematopoietic cell transplantation (allo‐HCT) is a potentially curative treatment for acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL). While many factors influence the outcomes of allo‐HCT, the independent impact of donor–recipient ABO mismatching remains unclear. Using the Center for International Blood and Marrow Transplant Research (CIBMTR) database, we identified patients aged ≥18 years with AML or ALL who underwent allo‐HCT between 2008 and 2018. Our objectives were to analyze the outcomes of allo‐HCT based on the donor–recipient ABO status (match, minor mismatch, major mismatch, bidirectional mismatch). Among 4946 eligible patients, 2741 patients (55.4%) were ABO matched, 1030 patients (20.8%) had a minor ABO mismatch, 899 patients (18.1%) had a major ABO mismatch, and 276 patients (5.6%) had a bidirectional ABO mismatch. In multivariable analyses, compared to ABO matched allo‐HCT, the presence of a major ABO mismatch was associated with worse overall survival (HR 1.16, 95% CI 1.05–1.29; p  = 0.005), inferior platelet engraftment (HR 0.83, 95% CI 0.77–0.90; p  < 0.001), and higher primary graft failure (HR 1.60, 95% CI 1.12–2.30, p  = 0.01). Relapse, acute graft versus host disease (GVHD) grades III‐IV and chronic GVHD were not significantly associated with ABO status. While donor age was not significantly associated with outcomes, older recipient age was associated with worse survival and non‐relapse mortality. Our study demonstrates that donor–recipient ABO status is independently associated with survival and other post‐transplantation outcomes in acute leukemia. This underscores the importance of considering the ABO status in donor selection algorithms and its impact in acute leukemia.